(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ivayani, Widiastuti A, Suryanti, Suharjo R, Priyatmojo A. 2022. Short Communication: First report of Xanthomonas sacchari causing rice sheath rot disease in Lampung, Indonesia. Biodiversitas 23: 6463-6470. Rice sheath rot is recently reported as an emerging important rice disease in Indonesia, which can cause yield losses of up to 85%. Due to its potential loss, serious attention should be given on the disease. However, there is still limited information on the causal agent of the disease in Indonesia, especially from plant pathogenic bacteria. One bacterial isolate (LSE 33) was obtained from the sheath rot symptom of rice. Pathogenicity test revealed that bacteria produced symptoms that were similar to those obtained from the field. Based on the sequence analysis of 16S rRNA gene region, isolate LSE 33 was placed within group of the type strain and reference strains of Xanthomonas sacchari. Strain LSE 33 had 99.93% sequence similarity with Xanthomonas sacchari strain SAM 144 and strain AF 10 isolated from rice, and 99.35% similarity with strain LMG 471T isolated from sugarcane. To our knowledge, this is the first report of X. sacchari causing sheath rot on rice in Indonesia.